2015
DOI: 10.1128/jvi.00791-15
|View full text |Cite
|
Sign up to set email alerts
|

Nonneutralizing Antibodies Induced by the HIV-1 gp41 NHR Domain Gain Neutralizing Activity in the Presence of the HIV Fusion Inhibitor Enfuvirtide: a Potential Therapeutic Vaccine Strategy

Abstract: A key barrier against developing preventive and therapeutic human immunodeficiency virus (HIV) vaccines is the inability of viral envelope glycoproteins to elicit broad and potent neutralizing antibodies. However, in the presence of fusion inhibitor enfuvirtide, we show that the nonneutralizing antibodies induced by the HIV type 1 (HIV-1) gp41 N-terminal heptad repeat (NHR) domain (N63) exhibit potent and broad neutralizing activity against laboratory-adapted HIV-1 strains, including the drug-resistant variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Monoclonal antibodies (mAbs) are of growing importance for protective and pathogenic immune responses to viruses. At present, there are many therapeutic antibodies to treat viral infections under development, such as antibodies for HIV-1, SARS-CoV, MERS-CoV, Nipah and Hendra viruses, and H7N9 influenza virus [48,50,[60][61][62][63][64][65][66]. Fortunately, screening antibodies from the large naïve libraries has enabled the rapid development of high-affinity human mAbs, especially for the rapid response to the outbreak of emerging viruses and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) are of growing importance for protective and pathogenic immune responses to viruses. At present, there are many therapeutic antibodies to treat viral infections under development, such as antibodies for HIV-1, SARS-CoV, MERS-CoV, Nipah and Hendra viruses, and H7N9 influenza virus [48,50,[60][61][62][63][64][65][66]. Fortunately, screening antibodies from the large naïve libraries has enabled the rapid development of high-affinity human mAbs, especially for the rapid response to the outbreak of emerging viruses and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile to explore why the antibodies in the sera is able to enhance the anti-HIV-1 activity of AP3. Our recent study has demonstrated that T20’s anti-HIV-1 activity is enhanced by a non-neutralizing antibody directed against the NHR domain of the HIV-1 gp41 46 . We thus hypothesize that some of the anti-gp41 antibodies in HIV/AIDS patients may bind to a site in NHR domain adjacent to the AP3’s binding region, resulting in increased interaction between AP3 and NHR-trimer and enhanced antiviral activity of AP3.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1-mediated cell-cell fusion assay. A dye transfer assay was used to detect HIV-1 Env-mediated cell-cell fusion as described previously (20). H9/HIV-1 IIIB cells were labeled with a fluorescent reagent, calcein AM (Molecular Probes, Inc., Eugene, OR), and then incubated with MT-2 cells (ratio of 1:10) in 96-well plates at 37°C for 2 h in the presence or absence of the test peptide at graded concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Four fields per well were counted. The percentages of inhibition of cell fusion by peptides were calculated based on the data from all 12 fields observed, as described previously (20); IC 50 s were calculated by using the Calcusyn computer program (43), and lines of best fit were drawn using the Sigma Plot 10.1 program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation